2017
DOI: 10.1103/physrevb.95.161110
|View full text |Cite
|
Sign up to set email alerts
|

Thermomechanical stabilization of electron small polarons in SrTiO3 assessed by the quasiharmonic approximation

Abstract: We predict a predominance diagram for electron defects in the temperature-hydrostatic stress space for SrTiO 3 by combining density functional theory and the quasiharmonic approximation. We discovered two regimes where small polarons dominate: under tensile stress at lower temperature due to a larger relaxation volume of the defect , and under compressive stress at higher temperature due to a smaller and larger formation entropy. This provides a means to modulate the electronic conductivity via controlling the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 54 publications
1
12
0
Order By: Relevance
“…Both the Arrhenius and polaron models fit the temperature‐dependent conductivity equally well and the activation energy found here is similar to predicted migration barriers of polarons in oxygen deficient SrTiO 3‐x predicted from density functional theory . Additionally, if the measured conductivity and activation energy are due to Ti 3+ polarons, then based on first principles work they are likely associated with point defects, in addition to (by definition) the lattice deformation.…”
Section: Resultssupporting
confidence: 77%
“…Both the Arrhenius and polaron models fit the temperature‐dependent conductivity equally well and the activation energy found here is similar to predicted migration barriers of polarons in oxygen deficient SrTiO 3‐x predicted from density functional theory . Additionally, if the measured conductivity and activation energy are due to Ti 3+ polarons, then based on first principles work they are likely associated with point defects, in addition to (by definition) the lattice deformation.…”
Section: Resultssupporting
confidence: 77%
“…To be consistent with the notation used in computational studies on oxides and semiconductors, and with the defect notation employed here, small polarons will be represented by n X and p X for bulk electron and hole polarons localized on atom X, respectively. In SrTiO 3 , first‐principle calculations indicate bulk small hole polarons centered around an O atom (pO1) are stable, but bulk small electron polarons on Ti (nTi-1 or Ti 3+ ) are not favorable in most conditions . Defect stabilized small electron polarons on Ti (Ti 3+ complexes) were found to be stable in proximity to oxygen vacancies, but it is impractical with current computational capabilities to find local minima in the configuration space associated with every charged defect considered in this work.…”
Section: Introductionmentioning
confidence: 91%
“…Recent computational work has probed some properties of SrTiO 3 doped with K and Na, nonmetal elements like N, and transition metals like Fe, Mn, and Ni, but the results are not connected to a thermodynamic model of the defect chemistry. The role of small electron or hole polarons has also been investigated computationally . In discussing polarons, it is necessary to distinguish between bulk and defect stabilized polarons or, in the language used in conventional ceramics literature for small electron polarons, Ti 3+ , and Ti 3+ complexes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Ref. [44] it was suggested that this is a viable way to obtain the relaxation volume of charged defects in DFT supercells where the ambiguity of defining pressure in charged cells [45] is removed by fitting to an equation of state. We also note that the fractional volume change does not depend significantly on cell size, which is discussed in detail in SM, Sec.…”
Section: B Mechanical Effect Of Lithium Insertion Into Zromentioning
confidence: 99%